UPAYA DINAS KEBUDAYAAN DAN PARIWISATA DALAM PEMBANGUNAN KAMPUNG WISATA DI KELURAHAN TEBING TINGGI OKURA KECAMATAN RUMBAI PESISIR KOTA PEKANBARU TAHUN 2014-2016 - Suhada M., Ananta; Febrina, Rury (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The lack of tourist attractions in Pekanbaru, forcing the City Government of Pekanbaru to think of new tourist attractions that's worthy of being developed. This issue is finally answered after the City Government through the City Mayor set the Urban Village of Tebing Tinggi Okura in the Subdistrict of Rumbai Pesisir as one of the tourist destinations of Malay history and culture. However, the efforts of Department of Culture and Tourism and other related Departments in implementation of developing this tourist attraction is still classified as weak and slow. Furthermore, there is no masterplan is also one of the problems so that the development budgets of the Tourism Village has yet to be arranged. This study intend to describe the efforts of the Department of Culture and Tourism in implementation of Tourism Village development at the Urban Village of Tebing Tinggi Okura in 2014-2016 and also to find out the factors that affects the slow performance of Department of Culture and Tourism in the development of Tourism Village in Urban Village of Tebing Tinggi Okura. This research using descriptive qualitative research methods, with the selection of informants using purposive sampling technique, where the subjects of this research are: Section Chief of Recreation and Entertainment of Department of Culture and Tourism, Urban Village Head of Tebing Tinggi Okura, and the Group Leader of Tourism Awareness. This research was done in Urban Village of Tebing Tinggi Okura in the Subdistrict of Rumbai Pesisi, Pekanbaru. Data collection techniques used is in-Depth Interview, observation, and documentation. The results of this research showed that the efforts of the Department of Culture and Tourism in the development of tourism in the Urban Village of Tebing Tinggi Okura in 2014-2016 is the Government formed the Group of Tourism Awareness that intend to develope tourist destinations in Tourism Village of Okura that fits to each job. Furthermore, the Government is running a test of the dock and the water bus to make it easier for the tourist to come to Tourism Village of Okura. The internal factors that affect the performance of Department of Culture and Tourism in developing Tourism Village of Okura are lack of budgets and there are no masterplan, also Tourism Village of Okura are not priority in Renja nor Restra.